2017
DOI: 10.3390/rs9121259
|View full text |Cite
|
Sign up to set email alerts
|

Co-Orbital Sentinel 1 and 2 for LULC Mapping with Emphasis on Wetlands in a Mediterranean Setting Based on Machine Learning

Abstract: Abstract:This study aimed at evaluating the synergistic use of Sentinel-1 and Sentinel-2 data combined with the Support Vector Machines (SVMs) machine learning classifier for mapping land use and land cover (LULC) with emphasis on wetlands. In this context, the added value of spectral information derived from the Principal Component Analysis (PCA), Minimum Noise Fraction (MNF) and Grey Level Co-occurrence Matrix (GLCM) to the classification accuracy was also evaluated. As a case study, the National Park of Kor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
90
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(107 citation statements)
references
References 66 publications
(61 reference statements)
5
90
0
Order By: Relevance
“…Given the promising results achieved by [26,74] with the RADARSAT-2 C-band when mapping savannah woody vegetation structure and by [75] who combined the Sentinel-1 C-band and Sentinel-2 data (with improved spatial, spectral and temporal resolutions compared to the Landsat data used in this study) in order to map land cover in a Mediterranean environment (overall accuracy =~94%, k = 0.928), it is anticipated that the synergy between the two Sentinels should provide considerable support in the efforts to accurately map savannah land cover.…”
Section: Landsat or Palsar? Or Both?mentioning
confidence: 99%
“…Given the promising results achieved by [26,74] with the RADARSAT-2 C-band when mapping savannah woody vegetation structure and by [75] who combined the Sentinel-1 C-band and Sentinel-2 data (with improved spatial, spectral and temporal resolutions compared to the Landsat data used in this study) in order to map land cover in a Mediterranean environment (overall accuracy =~94%, k = 0.928), it is anticipated that the synergy between the two Sentinels should provide considerable support in the efforts to accurately map savannah land cover.…”
Section: Landsat or Palsar? Or Both?mentioning
confidence: 99%
“…Furthermore, for crop types with similar phenological cycles, only using spectral information is still challenging for reliable discrimination of crop types. As synthetic aperture radar (SAR) can reflect the structure of vegetation, and optical imagery captures the multi-spectral information of crops, it has been indicated that the synergetic use of SAR and optical data can be complementary to each other [8,9].Space-borne SAR, due to its all-day, all-weather capability, wide coverage, and strong penetrating ability, has been increasingly used in crop classification, to complement with the use of optical imagery. It was found that considerable improvement can be achieved by increasing polarization channels [10,11].…”
mentioning
confidence: 99%
“…Furthermore, for crop types with similar phenological cycles, only using spectral information is still challenging for reliable discrimination of crop types. As synthetic aperture radar (SAR) can reflect the structure of vegetation, and optical imagery captures the multi-spectral information of crops, it has been indicated that the synergetic use of SAR and optical data can be complementary to each other [8,9].…”
mentioning
confidence: 99%
“…The method was selected as it has resulted in high accuracies in monitoring wetland dynamic. 50,51 The radial basis function that fits data in a higher dimensional space to increase class separability was implemented in EnMap toolbox. 52 All optical images were classified individually using the training data after which performance metrics were assessed by computing the overall and Cohen's-Kappa coefficient.…”
Section: Classificationmentioning
confidence: 99%